2020
DOI: 10.20525/ijrbs.v9i7.942
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of export diversification

Abstract: The main objective of this work is to identify the explanatory factors determining the diversification of exports in SADC countries during the period 1990-2018. We regress the indicator of export diversification, measured successively by the Herfindahl-Hirschman index on a set of explanatory variables. Using a next-generation panel data approach is applied, such as panel unit root, panel cointegration, fully modified OLS (FMOLS), and Dynamic Ordinary Least Squares (DOLS). The result of unit root tests for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Based on the estimation results, it can be seen that the GDP of the exporting country has the greatest influence on the diversification of exports of high-tech manufactured industrial commodities compared to the intensity of other technologies. This result is supported by research that finds that GDP has a positive and significant effect on export performance and export (Espoir, 2020;Agosin et al, 2012;Xing, 2018;Sekkat, 2016). Research conducted by Espoir (2020) found that GDP contributed positively and significantly to the export diversification process, and export diversification had a positive and significant impact on GDP growth.…”
Section: Robustness Testmentioning
confidence: 77%
See 2 more Smart Citations
“…Based on the estimation results, it can be seen that the GDP of the exporting country has the greatest influence on the diversification of exports of high-tech manufactured industrial commodities compared to the intensity of other technologies. This result is supported by research that finds that GDP has a positive and significant effect on export performance and export (Espoir, 2020;Agosin et al, 2012;Xing, 2018;Sekkat, 2016). Research conducted by Espoir (2020) found that GDP contributed positively and significantly to the export diversification process, and export diversification had a positive and significant impact on GDP growth.…”
Section: Robustness Testmentioning
confidence: 77%
“…This result is supported by research that finds that GDP has a positive and significant effect on export performance and export (Espoir, 2020;Agosin et al, 2012;Xing, 2018;Sekkat, 2016). Research conducted by Espoir (2020) found that GDP contributed positively and significantly to the export diversification process, and export diversification had a positive and significant impact on GDP growth. The results of this study are also supported by the research of Agosin et al (2012), which states that the GDP growth of an exporter country will be able to assist in the process of developing new sectors in export commodities so that export diversification can be achieved.…”
Section: Robustness Testmentioning
confidence: 77%
See 1 more Smart Citation
“…The TI was ideal because it did not rely on exports, unlike the export diversification index. Furthermore, it considered the complexities within the economy relative to the Herfindahl-Hirshman index and concentrated on the contribution of each sector based on weighted averages relative to the entropy index which assumes an equi-proportional distribution (Bebczuk and Daniel Berrettoni 2006;Espoir 2020;Takada et al 2020). There are 5 steps involved in calculating the TI (Quantec easydata 2021):…”
Section: Methodsmentioning
confidence: 99%
“…No clear-cut expectation can be made about the sign of trade openness. As emphasized by Espoir (2020), on the one hand, Ricardian trade models suggest that openness to trade should lead countries to specialise in their comparative advantage. On the other hand, greater openness to trade may also be associated with less protectionism, which tends to foster the expansion of tradable sectors.…”
Section: Econometric Modelmentioning
confidence: 99%